PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. ASTRA HONDA MOTOR DI CIKAMPEK - Winda Lia Septiani; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The purpose of this study was to determine how the relationship and influence of leadership and motivation to employees performance at PT. Astra Honda Motor. The research method was used with Explanatory Analysis approach that explains the causality relationship between variables. Sampling technique was using saturated sample, all members of the population were sampled. From this research result was found there is a relationship and influence which is significant between the variables of leadership motivation to employee performance at PT. Astra Honda Motor among variables by using the test F, where F count larger than F table (32.173 > 3.158). Conclusion: There is a significant effect that can be explained by the result obtained from the R-square is 0530, which means that the variables of leadership and motivation are giving contribution of 53.0% to the variable of employees performance at PT. Astra Honda Motor, while the remaining 47.0% was contributed by other variables which not researched. Suggestions which the author convey to company, leadership which was contained in the company would need to be more increased, considers motivation of employees was good enough.